Penguatan Usaha Kecil Menengah di Desa Sukamaju melalui Pendampingan Pembuatan Nomor Induk Berusaha (NIB) sebagai Upaya Legalitas Usaha - Ruswandi, Wawan; Hamidi, Dendi Zainuddin; Ginanjar, Heri; Sunarti, Ucu; Firdatul Anifah; Maryam, Siti; Ribuansyah, Morina Juliawati; Nabila, Salma Salsa; Wandayanti, Rahayu; Fadilah, Sultan Syahid; Wijaya, Cahya Sastra (Indra Institute Research & Publication, 2025)
This community service activity aims to strengthen the institutional capacity of Micro, Small, and Medium Enterprises (MSMEs) in Sukamaju Village through facilitation of business legality, especially by issuing a Business Identification Number (NIB). The implementation method uses a participatory and applicative approach by implementing the direct action method, where lecturers and students play an active role as facilitators. The entire series of activities is carried out in a structured manner, starting from the coordination stage with village officials, data collection of MSME actors, collection of identity documents, to submission of data to the relevant agencies for the business legality registration process through the Online Single Submission (OSS) system. The final stage includes socialization activities regarding the benefits of business legality and symbolic submission of NIB documents to MSME actors, involving the active role of village officials as implementing partners. The evaluation results show that the method used has proven effective in increasing MSME participation, accelerating the process of obtaining business legitimacy, and reducing administrative obstacles, especially those related to digital literacy. The main obstacles found were the low understanding of technology among MSME actors and the limited time for collecting administrative documents. Nevertheless, this activity provides a real contribution to the acceleration of business legality at the village level, while strengthening the synergy between academics, village governments, and related technical agencies. The success of this program is also in line with the findings of previous studies that emphasize the importance of direct assistance in supporting the digital business legalization process among MSMEs